2023
DOI: 10.3390/ani13142372
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Approach to Providing Environmental Enrichment to Pigs and Broiler Chickens Housed in Intensive Systems

Abstract: In Europe, regulations contain guidance to maintain high standards of animal welfare. In many parts of the world, large buyers for supermarkets or restaurants are the main enforcers of basic animal welfare standards. They can have considerable influence on improving standards on large commercial farms. Research clearly shows that straw is one of the most effective environmental enrichment for pigs. On some large farms, there are concerns that straw will either clog waste management systems or bring in disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
1
1
0
1
Order By: Relevance
“…Different enrichment programs in commercial broiler houses may influence diverse behavioral and physiological impacts on birds to improve welfare. Therefore, it is important to determine enrichment(s) that the animals will actively engage with, and several effective enrichment objects for broiler chickens have been suggested including ramps, platforms, and gradient lighting [42]. An enriched lighting program (VL_Con) was effective in improving birds' voluntary natural activity and engagement compared to 20 lx program (20 lx_Con) in this study and the previous study [10], indicating the improvement of comfort natural behavior using the VL lighting program.…”
Section: Discussionsupporting
confidence: 51%
“…Different enrichment programs in commercial broiler houses may influence diverse behavioral and physiological impacts on birds to improve welfare. Therefore, it is important to determine enrichment(s) that the animals will actively engage with, and several effective enrichment objects for broiler chickens have been suggested including ramps, platforms, and gradient lighting [42]. An enriched lighting program (VL_Con) was effective in improving birds' voluntary natural activity and engagement compared to 20 lx program (20 lx_Con) in this study and the previous study [10], indicating the improvement of comfort natural behavior using the VL lighting program.…”
Section: Discussionsupporting
confidence: 51%
“…It has been reported that listening to music has positive effects on social stress by reducing cortisol levels and even increasing the intensity of positive emotions due to the activation of cerebral structures related to emotions such as pleasure (Figure 2) [45][46][47][48][49][50]. In animals (e.g., pigs, dogs, chickens, buffaloes, and laboratory animals) [51,52], music has shown beneficial effects by reducing aggressive behavior, stress, and anxiety, considering it a sensory enrichment [53][54][55][56]. Neural pathways of music-evoked emotions.…”
Section: Auditory Stimulation In Dairy Cowsmentioning
confidence: 99%
“…W ostatnich latach pojawił się trend wykorzystania fal dźwiękowych jako formy muzykoterapii [Gueguen i in. 2023, Grandin 2023.…”
Section: Wyniki I Ich Omówienieunclassified